Whence karma?. (October 2023) - Bronkhorst, Johannes
How did the belief in rebirth and karmic retribution come into existence? W. D. Whitney called it 'one of the most difficult questions in the religious history of India', and Richard Salomon described it, a century later, as 'the single greatest problem of Indological studies'. Scholars have proposed textual continuities leading up to texts that give expression to this belief, but questions can be and have been raised about such continuities. Worse, these studies do not deal with the observation made by A. B. Keith almost a century ago, viz., that 'while the ideas thus recorded are of some value … the importance of transmigration lies precisely in the fact that the doctrine is an ethical system'. The one scholar who fully recognises the importance of ethicisation is Gananath Obeyesekere. Unfortunately, his theory is based on some disputable assumptions, which weaken it, as they weaken Richard Seaford's theory, which builds on Obeyesekere's ideas. This article offers an altogether different approach that puts this belief in line with beliefs that accompanied the appearance of social complexity elsewhere in the world.